The developing role of clofarabine in acute leukemias (Hematology Meeting Reports, 2009)
Nucleoside analogs count among the most active components of anticancer therapies.1,2 Through DNA incorporation and inhibition of ribonucleotide reductase (RnR), an enzyme involved in the recycling of the celluar nucleotide pool, their effects result in termination of DNA chain elongation, inhibition of DNA synthesis, interference with DNA repair mechanisms, and finally apoptosis.3,4 Several nucleoside analogs have become an integral part of treatment for a diverse range of malignancies. Cytarabine (1-β-D-arabinosylcytosine, ara-C) is used predominantly for therapy of patients with acute myeloid leukemias (AML) whereas the main spectrum of activity of gemcitabine (2’,2’-difluorodeoxycytidine), is in solid tumor malignancies.5,6 Fludarabine (9-β-D-arabinofuranosyl-2-fluoro-adenine 5’-monophosphate) and cladribine (2-chlorodeoxyadenosine, 2-CdA) have been among the first clinically useful purine nucleoside analogs and both are highly active in indolent lymphoproliferative disorders.7 An intriguing aspect of nucleoside analogs thus remains how apparently minor alterations in structure can result in major differences with respect to pharmacology, metabolism, and spectrum of activity.